Implikasi Praperadilan Terhadap Pelaksanaan Kewenangan Penyidik Kepolisian Dalam Sistem Peradilan Pidana - Bawono Sekti, Luluk Tirto; Junaidi, Muhamad; Arifin, Zaenal (Universitas Semarang, 2024)
The aim of this research is to analyze the implications of the implementation of police investigative authority in the criminal justice system and to determine the obstacles that occur as well as coercive efforts made in investigations and prosecutions by authorized institutions so that they can be controlled through the system pretrials. This research discusses the implications and authority of police investigators in the criminal justice system and the role of pre-trial as one of the legal measures for the protection and rights of suspects in examinations at the investigative level, as well as what factors can create obstacles to the protection of suspects' rights. Pre-trial arrangements are regulated in Article 77 of the Criminal Procedure Code, namely examining the validity or not of coercive efforts to arrest and detain as well as checking whether or not the termination of investigation or prosecution, compensation, and rehabilitation is valid. The method used is normative empirical, which is the addition of data or empirical elements from field studies to obtain data by holding questions and answers with police institutions. The result of this study is to find out about the implications of investigator authority in criminal justice and the reasons for pretrial efforts made by suspects rejected or granted by the local district court. Tujuan dari penelitian ini guna menganalisa implikasi terhadap pelaksanaan kewenangan penyidik kepolisian dalam sistem peradilan pidana dan untuk mengetahui kendala yang terjadi serta upaya paksa yang dilakukan dalam penyidikan maupun penuntutan oleh lembaga yang berwenang, sehingga dapat dikontrol melalui sistem praperadilan. Penelitian ini membahas bagaimana implikasi serta kewenangan penyidik kepolisian dalam sistem peradilan pidana dan bagaimana peranan praperadilan sebagai salah satu upaya hukum terhadap perlindungan dan hak-hak tersangka dalam pemeriksaan pada tingkat penyidikan, serta faktor apa sajakah yang dapat menjadikan hambatan tentang perlindungan hak-hak tersangka. Pengaturan praperadilan diatur dalam pasal 77 KUHAP yaitu memeriksa sah atau tidaknya upaya paksa pada penangkapan dan penahanan serta memeriksa sah atau tidaknya penghentian penyidikan atau penghentian penuntutan, ganti rugi dan rehabilitasi. Metode yang digunakan adalah normatif empiris , studi lapangan untuk memperoleh data-data dengan mengadakan tanya jawab dengan institusi kepolisian. Hasil dari penelitian ini adalah dapat mengetahui implikasi kewenangan penyidik dalam peradilan pidana dan sebab upaya praperadilan yang dilakukan oleh tersangka ditolak atau dikabulkan oleh pengadilan negeri setempat.